(untitled) (Research, Society and Development, 2022)
The lack of knowledge of the number of institutions working for the rescue and adoption of dogs and cats in Brazil, as well as the lack of data on internal and external policies, hinders the implementation of procedures to ensure the health and welfare of abandoned animals and animals in shelter. This research aimed to evaluate the profile of Brazilian shelters in relation to their internal and external policies in order to understand the reality of this theme in Brazil. The data from the shelters were collected through an online form applied in a distance learning extension course. The number of data considered in this study totaled 352 shelters. Most shelters were private (67.9%; 239/352) and there was representation from the five regions of Brazil and 22 states. It was possible to understand the profile of Brazilian shelters in relation to their external and internal policies related to the identification and reception of animals, physical structure, preventive management, diseases, and the animals’ departure. From the data presented, it was possible to observe the lack of public policies for the prevention of abandonment and population management, as well as the lack of applicability of protocols and management related to Shelter Medicine. The results of our study provide a starting point for Brazil to compare its policies and management performance with other countries, and to reevaluate existing strategies to improve the efficiency of the practices performed with abandoned animals in shelters and adoption institutions.